GENDER COMPARISON OF ATTITUDE OF SENIOR SECONDARY SCHOOL STUDENTS TOWARDS MATHEMATICS IN EKITI STATE, NIGERIA - Adebule, Samuel Olufemi; Aborisade, Olatunbosun James (European Scientific Journal, ESJ, 2014)
This study investigated the comparison of male and female Senior Secondary School students’ attitude towards mathematics. The study employed descriptive research design of the survey type. The population for the study consisted of all senior secondary school students in Ekiti state, Nigeria. The sample for the study was six hundred [600] senior secondary school students consisting of 300 males and 300 females selected from 12 senior secondary schools using multistage, stratified and purposive random sampling techniques .The mathematics attitude scale constructed and validated by the researchers was adopted and used as instrument for gathering data . The study shows that the attitude of students towards mathematics did not depend upon sex. Therefore, it is recommended that sex should not be considered as a factor influencing the attitude of students towards mathematics and those teachers should teach mathematics freely among the students of different sexes.